Efficiency of 13th-century acoustic ceramic pots in two Swiss churches - Victor Desarnaulds (2001)
This paper presents the results of field measurements in two churches in Switzerland (Villette and Syens) regarding their acoustic behavior with and without the use of their four thirteenth-century acoustic pots on the ceiling or walls at the altar area. The goal was to determine if the pots (average opening diameter: 88 mm) were acoustically significant in these two small churches (volume about 910 m3). The measured parameters were: resonance frequency, Leq, RT, EDT, STI, RASTI and C50. The answer that our measurements imply is negative. The measurements taken do not make it possible to highlight a real difference between the two configurations: open and closed pots. The weak variations that were observed on the values of C50, EDT and STI make very unlikely an audible improvement of the acoustics of these churches by the insertion of the pots. However, it is necessary to be careful and not to deduct too quickly from this preliminary study the inefficiency of the acoustic pots (it will probably depend on the church in question, the number and characteristics of pots and their positions within the church). Acoustic potentialities (diffusion, absorption and amplification) of such particular devices are discussed.